A new species of Archithosia Birket-Smith, 1965 in the subgenus Eurythosia Krüger, 2015 from Uganda (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Durante, Antonio; Potenza, Luigi; Pellegrino, Gabriele (Zootaxa, 2024)
As part of a study of the genus Archithosia Birket-Smith as a whole, this article focuses on the subgenus Eurythosia Krüger, describing a new species from Uganda: Archithosia henricus Durante, Potenza, and Pellegrino n. sp. The authors compare this new species with the other five species previously included in the subgenus, basing their diagnosis primarily on the male genitalia.